Cooperatives at work - Cheney, George; Noyes, Matt; Do, Emi; Vieta, Marcelo; Azkarraga, Joseba; Michel, Charlie (Emerald Publishing Limited, 2023)
For too long, cooperatives have been considered marginal players in the global economy, and as unrealistic venues for the aspirations of new and experienced members of the labour force. This marginalization shows in business, municipal and legal discussions, and curricula, where cooperative structures are rarely mentioned, let alone presented as viable options. Cooperatives at Work presents a range of success stories in employee ownership and worker owned-and-governed cooperatives. The authors further show how such firms embody important and highly contested ideals of democracy, shared equity, and social transformation. Throughout this volume, the authors present a range of practical lessons, strategies, and resources based on their pioneering, international research. This latest volume in The Future of Work series has a strong ethical stream, consistent with yearnings for more inspired forms of business revealed in many public opinion polls. The book is future-oriented, using contemporary as well as historical examples to teach lessons that are not necessarily time-bound. It is essential for anyone seeking a window onto the future of cooperative entrepreneurial practice and grassroots democracy.
Keywords: Producer cooperatives.; Profit-sharing.; Management -- Employee participation.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books